Study of Escherichia coli as a Cause of Diarrhoea in the Ashanti Region of Ghana - Awuah, Frank; Addo, Mathew Glover; Ofori, Linda Aurelia (European Scientific Journal, ESJ, 2023)
Even though diarrhoeagenic Escherichia coli (E. coli) is accepted worldwide as essential diarrhoea-causing agent, especially among children, routinely they are not sought as a stool sample pathogen in many microbiological laboratories. The conventional biochemical means are not able to differentiate E. coli which is a normal flora in the gastrointestinal tract from the pathogenic strains. This research work sought to detect and identify diarrhoeagenic E. coli in the Ashanti region of Ghana by using conventional multiplex PCR. A convenient sampling method was employed to select a total of 502 patients from Ashanti Regional and St. Michael’s Hospitals for the study. In all, five pathotypes of diarrhoeagenic E. coli were detected with enterotoxigenic E. coli (ETEC) as the most frequent. The target genes considered for each group of diarrhoeagenic E. coli were eaeA (E. coli attaching- effacing) and bfpA (bundle forming pilus A) for enteropathogenic E. coli (EPEC), elt and Stla for enterotoxigenic E. coli (ETEC), ial for enteroinvasive E. coli (EIEC), CVD432 for enteroaggregative E. coli (EAEC), and hlyA for enterohaemorrhagic E. coli (EHEC). Generally, some of the participants (31.08% = n/N= 69/222) exhibited symptoms of diarrhoea while others did not (68.92% = n/N =153/222 ), although they were positive for the pathotypes. The virulence factors considered were seen as contributory factors to the symptomatic situations. Participants in the ≤5 and ≥ 42-year groups were seen to be more vulnerable to diarrhoea. Additionally, it was discovered that men were more susceptible to diarrhoea than women. The study therefore recommends more studies into the ≥ 42-year group not neglecting that of children. In addition, this current study suggests the routine utilization of molecular methods such as conventional multiplex PCR to identify and detect the pathotypes of E. coli causing diarrhoea.